Participatory Management Model for Sustainability of Wetlands: Structural Model Analysis - Akbari, Roya; Mirdamadi, Seyed Mehdi; Hosseini, Seyed Jamal Farajollah; Lashgarara, Farhad (Journal of Environmental Accounting and Management, 2026)
Wetlands are indispensable ecosystems and play a crucial role in the stability of their periphery ecosystems. However, wetlands need to be managed in a sustainable way to ensure that not only the present but also the future benefits continue to accrue. As a result, this study proposes and validates a participatory pattern of sustainability management for important saline wetlands in Iran at the plain of Masileh in Qom province. The sample of the study was 251 experts in the field, recruited to answer a questionnaire related to participatory management and the related factors. Data analysis in this study was performed through structural equation modeling using LISREL software. The results showed that economic, environmental, and socio-cultural mechanisms have significant and positive effects on participatory management of wetlands. Moreover, beneficiaries related factors such as consultation, motivation, relationships, and rights have significant and positive effects on the social, environmental, and economic mechanisms and consequently on participatory management of the wetlands under study. In conclusion, this study’s findings suggest that policymakers and related parties should pay more attention to the participatory model for the conservation and sustainable management of wetlands ecosystems.